Assessment of emissions and exposure in 3D printing workplaces in Taiwan. - Chuang, Yung-Sheng; Berekute, Abiyu Kerebo; Hsu, Hsuan-Yu; Wei, Ho-Sheng; Gong, Wen-Cheng; Hsu, Ya-Yuan; Tsai, Chuen-Jinn; Yu, Kuo-Pin (Journal of Occupational & Environmental Hygiene, 2024)
Three-dimensional (3D) printing is an emerging and booming industry in Taiwan. Compared to traditional manufacturing, 3D printing has various advantages, such as advanced customization, additive manufacturing, reduced mold opening time, and reduced consumption of precursors. In this study, the real-time monitoring of particulate matter (PM) and total volatile organic compound (TVOC) emissions from various filaments is investigated using fused deposition modeling with material extrusion technology, a liquid-crystal display, a stereolithography apparatus based on vat photopolymerization technology, and binder jetting for occupational settings. An exposure assessment for nearby workers using the 3D printing process was performed, and improvement measures were recommended. Nine 3D printing fields were measured. The generation rate of ultrafine particles ranged from 1.19 × 1010 to 4.90 × 1012 #/min, and the geometric mean particle size ranged from 30.91 to 55.50 nm. The average concentration of ultrafine particles ranged from 2.31 × 103 to 7.36 × 104 #/cm3, and the PM2.5 and PM10 concentrations in each field ranged from 0.74 ± 0.27 to 12.46 ± 5.61 μg/m3 and from 2.39 ± 0.60 to 30.65 ± 21.26 μg/m3, respectively. The TVOC concentration ranged from 0.127 ± 0.012 to 1.567 ± 0.172 ppm. The respiratory deposition (RDUFPs) dose ranged from 2.02 × 1013 to 5.54 × 1014 nm2/day. Depending on the operating conditions, appropriate control and protective measures should be employed to protect workers' health.